Pengaruh kejelasan sasaran anggaran, pengendalian akuntansi dan sistem pelaporan terhadap akuntabilitas kinerja instansi pemerintah (studi pada satuan kerja perangkat daerah kabupaten rokan hulu) - Wahyuni '; Raja Adri Satriawan; Enni Savitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
The research aims to look at the empirical evidence the effects of budget goal clarity, accounting control, and reporting system on performance accountability of public institutions. in Rokan Hulu. The research uses a survey of the work unit Rokan Hulu district.The samples used were as many as 60 people were respondents. The population in this study was 31 on education in Rokan Hulu. The type of data used is primary data by using questionnaire method of data collection. The method of data analysis used in this study is multiple regression (multiple regression).The results showed that budget goal clarity effects on performance accountability of public institutions, budget goal clarity is done the better or greater, the greater the performance accountability of public institutions. Accounting controls do not affect on performance accountability of public institutions, because the budget is drawn up clearly with the available resources are not able to be lame effectively and efficiently which could potentially lead to fraud and inequality budget occurs. Reporting system affects on performance accountability of public institutions because good reporting system to monitor and control the performance of officials in implementing the set budget.Keywords: budget goal clarity, accounting control, reporting systems, performance accountability of public institutions.